2009
DOI: 10.1002/ijc.24244
|View full text |Cite|
|
Sign up to set email alerts
|

Liposomal honokiol inhibits VEGF‐D‐induced lymphangiogenesis and metastasis in xenograft tumor model

Abstract: Lymph nodes metastasis of tumor could be a crucial early step in the metastatic process. Induction of tumor lymphangiogenesis by vascular endothelial growth factor-D may play an important role in promoting tumor metastasis to regional lymph nodes and these processes can be inhibited by inactivation of the VEGFR-3 signaling pathway. Honokiol has been reported to possess potent antiangiogenesis and antitumor properties in several cell lines and xenograft tumor models. However, its role in tumor-associated lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…In solid tumors, VCAM-1-targeted liposomes can prevent endothelial cell activation and function through TNF-a binding [134] and any agent with a high affinity to a peculiar MMP type or integrin ligand-conjugated PEG-liposomes loaded with doxorubicin can target both tumor angiogenesis and tumor cells [135,136]. Positively charged liposomal nanoparticles might also be used to deliver plaxitel to endothelial cells [137], deliver pro-inflammatory mediators to macrophages [138] and deliver Honokiol, an inhibitor of VEGF-induced autophosphorylation of VEGF receptor 2, to lymphocytes [139]. Interestingly, the targeted delivery of siRNA through CD44 targeting hyaluronic acid based selfassembling nanosystems, an approach still investigated in solid tumors, might also be effective in AML as LSCs are more dependent on CD44 than HSCs [140].…”
Section: Potential Targetsmentioning
confidence: 99%
“…In solid tumors, VCAM-1-targeted liposomes can prevent endothelial cell activation and function through TNF-a binding [134] and any agent with a high affinity to a peculiar MMP type or integrin ligand-conjugated PEG-liposomes loaded with doxorubicin can target both tumor angiogenesis and tumor cells [135,136]. Positively charged liposomal nanoparticles might also be used to deliver plaxitel to endothelial cells [137], deliver pro-inflammatory mediators to macrophages [138] and deliver Honokiol, an inhibitor of VEGF-induced autophosphorylation of VEGF receptor 2, to lymphocytes [139]. Interestingly, the targeted delivery of siRNA through CD44 targeting hyaluronic acid based selfassembling nanosystems, an approach still investigated in solid tumors, might also be effective in AML as LSCs are more dependent on CD44 than HSCs [140].…”
Section: Potential Targetsmentioning
confidence: 99%
“…99 Exploration exhibited that VEGF-C and VEGF-D enhanced lymphangiogenesis, the metastatic spread of malignant cells to lymph nodes. 100,101 Honokiol is a potential antiangiogenic and antitumor medicine that acts by blocking VEGF-induced autophosphorylation of VEGF receptor 2. To investigate related lymph node metastasis and antitumor activity, liposomal honokiol was injected intraperitoneally in a mouse model of xenografted Lewis lung carcinoma cells overexpressing VEGF-D. Liposomal honokiol markedly reduced metastasis to the lymph nodes when compared with the control group.…”
Section: Targeting To Tumor-associated Lymphocytesmentioning
confidence: 99%
“…Previous studies have shown that lymphangiogenesis was closely associated with an increased risk of lymph node metastasis. If lymphangiogenesis-related properties of LECs were inhibited, the risk of lymphatic dissemination was significantly reduced (Wen et al, 2009). Therefore, cancer-induced lymphangiogenesis is essential for the invasion and secondary lymphatic metastasis.…”
Section: Lymphangiogenesis and Lymphatic Metastasis In Hnsccmentioning
confidence: 99%